Poorly differentiated biphasic synovial sarcoma of the vulva, displaying SS18::SSX1 fusion and weak to absent (mosaic) INI1/SMARCB1 immunostaining: A rare case with literature review - Bharat Rekhi; Sheenal Bhatia; Omshree Shetty; Amita Maheshwari (Indian Journal of Pathology and Microbiology)
Synovial sarcoma (SS) is rarely documented in the female genital tract, especially confirmed by molecular testing for SYT::SSX translocation and TLE1 immunostaining. A 62-year-old lady presented with a progressively increasing lump and pain over her right groin, for 6-month duration. Radiologically, a well-defined, solid-cystic mass was seen involving the right labia with necrotic areas, sparing the underlying muscles and the overlying skin. She underwent a biopsy followed by a surgical excision. Histopathologic examination revealed a spindle cell sarcoma, including tumor cells exhibiting a prominent hemangiopericytomatous pattern. There were focal areas of epithelial differentiation (pseudoglandular) along with areas of round cell morphology and increased mitoses (poor differentiation) in the resected specimen. Immunohistochemically, the tumor cells were diffusely positive for TLE1, patchily positive for pan keratin (AE1/AE3) and EMA, the latter more in the areas of epithelial differentiation, while negative for CD34, SMA, desmin, S100P, and SOX10. INI1/SMARCB1 showed a characteristic weak to absent (mosaic) staining pattern. Furthermore, the tumor displayed SS18::SSX1 fusion by RT-PCR. This constitutes one of the few reported cases of vulvar SS, confirmed by molecular testing and the first documented vulvar SS showing a mosaic pattern of INI1/SMARCB1 immunostaining. A review of the literature and diagnostic implications are presented herewith.